Analysis of the Relationship between Adolescents Need for Reproductive Health Services and Barriers to Access to Reproductive Health Services for Adolescents in Bata Laiworu District, Muna Regency - Israyani, Wa Ode; Umi Nurlila, Ratna; Amraeni, Yunita (Waluya The International Science of Health Journal, 2024)
Introduction: Reproductive health problems are of particular concern, especially those that occur in Indonesian teenagers, both in terms of knowledge and actions for prevention and treatment that need to be taken into account. Based on Indonesian Demographic Health Survey Data, only a small number of young women aged 15 to 19 years have sufficient knowledge. Negative impacts on adolescent reproductive health can be avoided with good sexual and reproductive health information, both directly and indirectly, therefore it is interesting for researchers to conduct an analysis of the relationship between adolescent needs for reproductive health services and barriers to access to adolescent reproductive health services in Bata Laiworu District, Regency. Muna Method: Quantitative observational analytical research using a cross sectional approach, a population of 1,088 and a sample size of 285 students using lemeshow. The sampling method uses Proportional Random Sampling. Result: Based on the Chi Square test that has been carried out, it can be seen (continuity correction) with a p value of 0.000<0.05, meaning there is a relationship between adolescent needs and the use of adolescent reproductive health services. Conclusion: It is necessary for schools to consider including a reproductive health curriculum for students through more in-depth counseling guidance.